Assessment of the reliability of the motor unit size index (MUSIX) in single subject "round-robin" and multi-centre settings. Issue 5 (May 2019) - Alix, James J.P.; Neuwirth, Christoph; Gelder, Lucy; Burkhardt, Christian; Castro, José; de Carvalho, Mamede; Gawel, Malgorzata; Goedee, Stephan; Grosskreutz, Julian; Lenglet, Timothée; Moglia, Cristina; Omer, Taha; et al.
Highlights: Motor unit size index (MUSIX) is a rapid, non-invasive means of assessing reinnervation. Using healthy volunteers reliable data were provided by both experienced and non-experienced raters. Results across single subject and multi-centre settings demonstrate high reliability/reproducibility. Abstract: Objective: The motor unit size index (MUSIX) is incorporated into the motor unit number index (MUNIX). Our objective was to assess the intra-/inter-rater reliability of MUSIX in healthy volunteers across single subject "round robin" and multi-centre settings. Methods: Data were obtained from (i) a round-robin assessment in which 12 raters (6 with prior experience and 6 without) assessed six muscles (abductor pollicis brevis, abductor digiti minimi, biceps brachii, tibialis anterior, extensor digitorum brevis and abductor hallucis) and (ii) a multi-centre study with 6 centres studying the same muscles in 66 healthy volunteers. Intra/inter-rater data were provided by 5 centres, 1 centre provided only intra-rater data. Intra/inter-rater variability was assessed using the coefficient of variation (COV), Bland-Altman plots, bias and 95% limits of agreement. Results: In the round-robin assessment intra-rater COVs for MUSIX ranged from 7.8% to 28.4%. Inter-rater variability was between 7.8% and 16.2%. Prior experience did not impact on MUSIX values. In the multi-centre study MUSIX was more consistent than the MUNIX. Abductor hallucis was the least reliable muscle. Conclusions: The MUSIX is a reliable neurophysiological biomarker of reinnervation. Significance: MUSIX could provide insights into the pathophysiology of a range of neuromuscular disorders, providing a quantitative biomarker of reinnervation.